Authoritarian parenting style predicts poorer glycemic control in children with new‐onset type 1 diabetes. Issue 7 (8th August 2018) - Noser, Amy E.; Majidi, Shideh; Finch, Jonathan; Clements, Mark A.; Youngkin, Erin M.; Patton, Susana R.
Abstract : Objective: To examine cross‐sectional and longitudinal associations among parenting styles (ie, authoritative, authoritarian, and permissive) and youth glycated hemoglobin (HbA1c) in a cohort of families of children with new‐onset type 1 diabetes (T1D). Methods: One‐hundred two parents completed a baseline measure of parenting style, and we collected child HbA1c values at baseline and at three‐ and six‐month follow‐ups. We examined correlations among use of different parenting strategies and child HbA1cs. We conducted multiple regressions to assess the impact of these strategies on child HbA1c at three‐month and six‐month follow‐ups, while controlling for baseline HbA1c, family income, and T1D duration. Results: Correlational analyses showed negative associations between authoritative strategies and child HbA1c at baseline, three‐month, and six‐month assessments and positive associations between authoritarian strategies and child HbA1c at three‐month and six‐month assessments. Regression analyses found use of authoritarian‐like strategies were the only parenting strategies associated with child HbA1c at three‐month and six‐month follow‐ups, while controlling for baseline HbA1c, family income, and T1D duration. Conclusion: Parents' use of authoritarian‐like strategies may negatively impact glycemic control over the course of six‐month in children with new‐onset T1D.